## (X-2 / 5-x-2) / 3x-6 / 3-x is calculated (X-5 / 2) - X-2) / (3x-6 / 3-x)

=X-2 / 3-x) / 3-x / 3 X-6 3-x about 3x-6 = 3 (X-2) X-2 about 3x-6

=3

### 54 + 4x = 75 + X how much is x? Use equation

54+4X=75+X

4x-x = 75-54

3x=21

x=7

Potato troupe Shao Wenchao answers your questions

If you don't understand this question, you can ask,

### Calculation: X * x + 4x = 2, how much is x

x ²+ 4x=2

x ²+ 4x+4=6

(x+2) ²= six

x+2=±√6

x1=√6-2, x2=-√6-2

### Calculation: x ^ 2-9 / 4-x ^ 2 * x ^ 2 + X-2 / x ^ 2-4x + 3,

(x^2-9)/(4-x^2) * (x^2+x-2)/(x^2-4x+3)

=(x-3)(x+3)/(2-x)(2+x) * (x+2)(x-1)/[(x-1)(x-3)]

=(x+3)/(2-x)

### The positive integer solution of inequality group 2 (X-6) less than 3-x, (2x-1) / 3 - (5x + 1) / 2 less than or equal to 1 is ()

2x-12

### Find inequality 3 (x − 1) 2) Maximum integer solution of ≤ 2 (x − 3) + 1

Solving inequality 3 (x − 1)

2) ≤2(x−3)+1

De bracketed: 3x-3

2≤2x-6+1

Displacement: 3x-2x ≤ 3

2-6+1

Then x ≤ - 7

two

The maximum integer is - 4